A guess by an expert or a joint accumulation of experience? A study of the admission process in Swedish sport schools: perspectives from school sport teachers - Andersson, F.; Fahlström, P. G. (Sports Coaching Review, 2026)
In this article we use the concept of Communities of Practice (CoP) to understand how Swedish school sport teachers enact the admission process, the identification and selection of student athletes, to Swedish national upper secondary elite sport schools (SNESS). Data were gathered by conducting six focus group interviews involving 18 school sports teachers representing six different sports. The findings indicate that the admission process is influenced by and enacted through sport-specific CoPs and include a strategic identification of athletes, a set of tools - physical aptitude tests, sport-specific training, interviews, social activities - and documents (matrices, forms, interview-guides). While the process constitutes individual subjective assessments of athletes, the findings also imply that the teachers` common engagement is the central enterprise of their collective actions. The admission is a cooperative process where the teachers expend their collective competence, joint cumulative experience, to identify, assess, and select student athletes.